The role of diet and physical activity in PCOS - A Quick Review - Pawelec, Natalia; Mazur, Weronika; Hawajski, Artur; Jankowska, Natalia; Świerzyńska, Adrianna; Kapciak, Alicja; Górny, Julia; Naja, Katarzyna (Quality in Sport, 2025)
Introduction: Polycystic Ovary Syndrome (PCOS) is a condition commonly found in young women. It is associated with many possible health consequences, ranging from acne, hirsutism, and obesity to fertility problems and even the development of endometrial cancer. Treatment is tailored to the individual, depending on various complications and needs. However, it is important to note that in most cases, the first recommended step is lifestyle modification. Key components of this include a healthy diet and physical activity. These recommendations are often overlooked or undervalued, with patients frequently expecting immediate pharmacological treatment and not believing in the potential effects of lifestyle changes. Aim of Study: The purpose of this review is to explore and emphasize the crucial role of diet and physical activity in the management of women with PCOS. Material and methods: PubMed and Google Scholar databases were used for the research. Results and Conclusions: A well-balanced diet and regular physical activity play a crucial role in both the prevention and management of women with PCOS. While there are no specific diets or forms of physical activity recommended, research shows that any modifications towards eliminating unhealthy diet habits and sedentary lifestyles can significantly impact the quality of life for these women.